Fitness band accuracy in older community dwelling adults. (September 2019) - Madigan, Elizabeth A
Fitness bands are widely available and assist with tracking the number of steps taken. However, for older people with slow gaits, shorter step widths and/or use of ambulatory devices, the accuracy of fitness bands for step counting has not been well studied. Using four commercially available fitness bands (Garmin Vivofit2™, Fitbit Flex™, Up3™ and Microsoft Band™), we studied 30 older people with varying ambulatory abilities. We videotaped participants walking and compared the videotaped step count with the fitness band counts. Only 5 of the 30 participants had accurate readings within a ±20 percent accuracy for all four bands. There was no relationship between the step speed and accuracy of the fitness bands. Participants using walkers and walking sticks had none of the bands that met the ±20 percent accuracy. Canes were more variable with accuracy. Fitness band manufacturers may need to tune their algorithms for use by older people.